Pembelajaran Keterampilan Menulis Teks Cerita Pendek Siswa Kelas IX SMPN 4 Kota Bengkulu - Yani, Yaniarti; Joko Purwadi, Agus; Wulandari, Catur (Jurnal Korpus, 2025)
This study aims to describe the learning of short story writing skills for class IX students at SMP Negeri 4 Bengkulu City. The method used in this study is a qualitative descriptive method. The subjects in this study were teachers who carried out the planning, implementation, and assessment of learning and students who took part in learning the skills of writing short story texts for class IX of SMP Negeri 4 Bengkulu City. Data collection techniques used are observation, interviews, and documents. The results showed that at the planning stage, the teacher had fully loaded all of the RPP components, including identity, KI, and KD, formulation of indicators, formulation of learning objectives, teaching materials, learning resources, learning media, learning models, learning methods, learning steps, and assessment. All aspects of the RPP have been fully contained in the RPP prepared by the teacher based on the assessment of the RPP analysis, this is appropriate because the RPP prepared by the teacher is the result obtained from the modified subject teacher consultation (MGMP). At the implementation stage of learning, it shows that the teacher has carried out learning with a scientific approach, namely exploration, elaboration, and closure. The implementation of learning uses the Discovery Learning model through syntax, which is carried out as a form of strategy in an effort to find out through various activities so that the teacher plays a role as a guide for students. The learning assessment carried out was in accordance with the assessment technique based on the 2013 Curriculum. The teacher assessed attitudes, knowledge, and skills.